U0126: Not only a MAPK kinase inhibitor - You, Yijie; Niu, Yunlian; Zhang, Jian; Huang, Sheng; Ding, Peiyuan; Sun, Fengbing; Wang, Xuhui (Frontiers in Pharmacology, 2022)
U0126, as an inhibitor of the MAPK signaling pathway, is closely related to various biological processes, such as differentiation, cell growth, autophagy, apoptosis, and stress responses. It makes U0126 play an essential role in balancing cellular homeostasis. Although U0126 has been suggested to inhibit various cancers, its complete mechanisms have not been clarified in cancers. This review summarized the most recent and relevant research on the many applications of U0126 and described its role and mechanisms in different cancer cell types. Moreover, some acknowledged functions of U0126 researched in the laboratory were listed in our review. We discussed the probability of using U0126 to restain cancers or suppress the MAPK pathway as a novel way of cancer treatment.